Lipidomics of intact mitochondria by MALDI-TOF/MS - Roberto Angelini (Journal of Lipid Research, 2012)
A simple and fast method of lipid analysis of isolated intact mitochondria by means of MALDI-TOF mass spectrometry is described. Mitochondria isolated from bovine heart and yeast have been employed to set up and validate the new method of lipid analysis. The mitochondrial suspension is directly applied over the target and, after drying, covered by a thin layer of the 9-aminoacridine matrix solution. The lipid profiles acquired with this procedure contain all peaks previously obtained by analyzing the lipid extracts of isolated mitochondria by TLC and/or mass spectrometry. The novel procedure allows the quick, simple, precise, and accurate analysis of membrane lipids, utilizing only a tiny amount of isolated organelle; it has also been tested with intact membranes of the bacterium Paracoccus denitrificans for its evolutionary link to present-day mitochondria. The method is of general validity for the lipid analysis of other cell fractions and isolated organelles.